Investigating the Facebook experience through Q Methodology: Collective investment and a 'Borg' mentality. (October 2015) - Orchard, Lisa J; Fullwood, Chris; Morris, Neil; Galbraith, Niall
Several recent studies have explored social networking sites, such as Facebook, in light of the uses and gratifications approach. However, research has tended to ignore the latter part of this paradigm. This article uses Q methodology to explore user experiences of Facebook, allowing further exploration of gratification from site usage. Four distinct viewpoints were found: Facebook as a superficial environment; Facebook as a valid and valuable social environment; Facebook as an environment of surveillance; and Facebook as a destructive environment. Although the viewpoints show elements of user satisfaction, some users view Facebook in an almost entirely negative way. The article concludes by theorising a model of Facebook usage, drawing upon a metaphor from Star Trek, specifically an analogy with the Borg. It is argued that a level of 'collective investment' resides over social networks that may sometimes promote compliance.